2-Chlorophenyl-substituted benzofuro[3, 2-b]pyridines with enhanced topoisomerase inhibitory activity: The role of the chlorine substituent. Issue 15 (1st August 2017) - Thapa Magar, Til Bahadur; Kadayat, Tara Man; Lee, Hwa-Jong; Park, Seojeong; Bist, Ganesh; Shrestha, Aarajana; Kwon, Youngjoo; Lee, Eung-Seok
Graphical abstract: Abstract: A new series of 2-chloropheny-substituted benzofuro[3, 2- b ]pyridines were designed, synthesized, and evaluated for topoisomerase I and II inhibition and antiproliferative activity. Compounds17 –19, 23, 24, 26, and27 exhibited excellent topo II inhibitory activity. A systematic structure-activity relationship study revealed the important role of chlorine substitution in the strong topoisomerase inhibitory activity.